PANDANGAN TIGA TOKOH PEMBANGUN SAINS ISLAM DUNIA DAN BANGUNAN SAINS ISLAM MODEL INDONESIA: PENGALAMAN TIGA UIN - Anshori Anshori (Kopertais Wilayah X Jawa Tengah, 2013)
AbstractThree founders thinkers of relationship between science and religion or Islamic science builders (1) Seyyed Hossein Nasr, (2) Ziauddin Sardar, and (3) Mehdi Golshani have different characteritics, eventhough their three thinking were completing each other. Nasr is more for answering the deserting of the west thinking. Sardar is more systematic and methodologic but his tendency against the west. And Golshani is reconciliate with the formulation of “ Qawliyyah” and “Kawniyyah”, phisical and metaphisical, using science for approving trancedent reality. The scientific integration article or the new formulation relationship of modern science and Islam (scientific integration study case of Three Islamic State University UIN Syarif Hidayatullah Jakarta, UIN Sunan Kalijaga Yogjakarta, and, UIN Maulana Malik Ibrahim Malang), as the effort for developing Islamic science wholly. The writer tries hard to find out a specific character and color for developing Indonesian of Islamic science and aplicatif conceptual that is framed by science revolution and legacy of Islamic thought and the heritage as the spirit and motivation for developing Islamic science especially in Indonesia PANDANGAN TIGA TOKOH PEMBANGUN SAINS ISLAM DUNIA DAN BANGUNAN SAINS ISLAM MODEL INDONESIA: PENGALAMAN TIGA PANDANGAN TIGA TOKOH PEMBANGUN SAINS ISLAM DUNIA DAN BANGUNAN SAINS ISLAM MODEL INDONESIA: PENGALAMAN TIGA UIN